2014
DOI: 10.1085/jgp.201311038
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of altered hERG1 channel gating by small molecule activators

Abstract: Agonists bind to sites on all four subunits to activate human ether-a-go-go–related gene 1 (hERG1) K+ channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 50 publications
5
39
1
Order By: Relevance
“…RPR profoundly slows the rate of deactivation (Kang et al, 2005;Perry et al, 2007) and causes a modest positive shift in the voltage dependence of inactivation (Perry et al, 2007) of hERG1 channels. We previously reported that the biophysical properties and response to PD and ICA were similar for concatenated WT hERG1 tetramers (WT 4 ) and WT monomer channels formed by coassembly of single WT hERG subunits (Wu et al, 2014b). In this study, we compare RPR-altered deactivation and inactivation between these two types of WT channels.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…RPR profoundly slows the rate of deactivation (Kang et al, 2005;Perry et al, 2007) and causes a modest positive shift in the voltage dependence of inactivation (Perry et al, 2007) of hERG1 channels. We previously reported that the biophysical properties and response to PD and ICA were similar for concatenated WT hERG1 tetramers (WT 4 ) and WT monomer channels formed by coassembly of single WT hERG subunits (Wu et al, 2014b). In this study, we compare RPR-altered deactivation and inactivation between these two types of WT channels.…”
Section: Resultsmentioning
confidence: 87%
“…WT KCNH2 (HERG1, isoform 1a, National Center for Biotechnology Information Reference Sequence NM_000238) cDNA was cloned into the pSP64 oocyte expression vector, and mutations were introduced using the QuikChange site-directed mutagenesis kit (Agilent Technologies, Santa Clara, CA). Methods for constructing concatenated tetramers containing a variable number of WT and/or mutant KCNH2 cDNAs with defined positioning were the same as previously described (Wu et al, 2014b). In the text and figures, concatenated tetramers formed by four WT or L553A (LA) mutant subunits are designated as WT 4 and LA 4 , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concatenation of subunits can hERG1 Block and Inactivation affect the pharmacology of the resulting tetrameric channels (Wu et al, 2014b(Wu et al, , 2015. Therefore, we compared the concentration-response relationships for cisapride, dofetilide, and MK-499 on the block of concatenated WT hERG1 (WT 4 ) channels and channels formed naturally by coassembly of single WT subunits (WT monomer ).…”
Section: Resultsmentioning
confidence: 99%
“…Second, poor expression of mutant ERG2 channels coupled with interference from endogenous currents at negative potentials in oocytes prevented analysis of deactivation kinetics over a broad range of voltages. Third, a Hill coefficient .1 for the [RPR]-response relationships could indicate positive ligand-binding cooperativity or could result from cooperative subunit interactions, as we previously found for two other hERG1 activators, PD-118057 [2-[[4-[2-(3,4-dichlorophenyl) In our previous study of the effects of PD-118057 and ICA-105574 on concatenated hERG1 tetramers (Wu et al, 2014), we found that although subunit cooperativity contributes to the effects of these two hERG1 agonists, there was no change in EC 50 or the Hill coefficient as the number of drug binding sites was increased from one to four. This finding indicates that occupancy of one binding site did not lead to an enhancement of PD-118057 and ICA-105574 affinity of other sites.…”
Section: Rpr Has Differential Effects On Herg1 and Rerg2mentioning
confidence: 92%